Cytosolic abscisic acid activates guard cell anion channels without preceding Ca2+ signals. - Dietrich, Petra; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2005)
The phytohormone abscisic acid (ABA) reports on the water status of the plant and induces stomatal closure. Guard cell anion channels play a central role in this response, because they mediate anion efflux, and in turn, cause a depolarization-induced K+ release. We recorded early steps in ABA signaling, introducing multibarreled microelectrodes in guard cells of intact plants. Upon external ABA treatment, anion channels transiently activated after a lag phase of approximately 2 min. As expected for a cytosolic ABA receptor, iontophoretic ABA loading into the cytoplasm initiated a rise in anion current without delay. These ABA responses could be elicited repetitively at resting and at largely depolarized potentials (e.g., 0 mV), ruling out signal transduction by means of hyperpolarization-activated calcium channels. Likewise, ABA stimulation did not induce a rise in the cytosolic free-calcium concentration. However, the presence of approximately 100 nM background Ca2+ was required for anion channel function, because the action of ABA on anion channels was repressed after loading of the Ca2+ chelator 1,2-bis(2-aminophenoxy)ethane-N,N,N',N'-tetraacetate. The chain of events appears very direct, because none of the tested putative ABA-signaling intermediates (inositol 1,4,5 trisphosphate, inositol hexakisphosphate, nicotinic acid adenine dinucleotide phosphate, and cyclic ADP-ribose), could mimic ABA as anion channel activator. In patch-clamp experiments, cytosolic ABA also evoked anion current transients carried by R- and S-type anion channels. The response was dose-dependent with half-maximum activation at 2.6 microM ABA. Our studies point to an ABA pathway initiated by ABA binding to a cytosolic receptor that within seconds activates anion channels, and in turn, leads to depolarization of the plasma membrane.